Analysis of the performance in the linear field of Equivalent-Frame Models for regular and irregular masonry walls. (15th August 2017) - Siano, Rossella; Sepe, Vincenzo; Camata, Guido; Spacone, Enrico; Roca, Pere; Pelà, Luca
Highlights: EFM modelling accuracy for URM structures is validated by comparison with FEM models. The comparative analyses involved schemes with regular and irregular configurations. Non-dimensional parameters allowed exploring the limits for EFM applicability. Modelling recommendations derived by the analyses for improving EFM effectiveness. Abstract: The Equivalent-Frame Method (EFM), a simplified procedure for structural modelling of masonry constructions, is having a great success for the good balance that it allows between the accuracy of the geometrical description and the simplicity of the mechanical calibration. Despite the widespread use of EFM in scientific and professional field, some uncertainties affect its application to the specific problem of the existing unreinforced masonry (URM) buildings. For these structures, in fact, irregular geometries, the presence of deformable diaphragms and the interaction with other structures in aggregate configurations represent hard-to-model features that limit the accuracy of EFM. The paper presents a comparative study in the linear field between EFM and the more accurate Finite Element Method (FEM), assumed as reference. The comparative analysis involves a wide set of geometrical schemes, characterized by both regular and irregular configurations, and it is aimed at providing a measure of the EFM modelling accuracy as a function of the geometry of the wall. Non-dimensional parameters allow exploring the limits of applicability of EFM for both regular and irregular walls. Based on the parametric analyses, some recommendations are given for improving the effectiveness of the method and preserving the simplicity of application that makes EFM models so popular and widely used.